Integrasi Keilmuan Syariah dan Ilmu Hukum di Program Studi Perbandingan Mazhab UIN Syarif Hidayatullah Jakarta - Siti Hanna; Ahmad Sudirman Abbas; Ahmad Nur Hanafi; Navis Yusrizal (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2026)
The transformation policy of state universities is not merely limited to curriculum integration within study programmes; it also seeks to eliminate the dichotomy between religious sciences and general sciences. The Comparative Mazhab Study Programme at UIN Jakarta explores scholarship based on both positive law and Islamic law. This study addresses two main research questions: (1) How is the curriculum of sharia and legal sciences formulated in the Comparative Mazhab Study Programme, Faculty of Sharia and Law, UIN Jakarta? (2) How is the integration of these disciplines implemented within the curriculum? Employing a qualitative descriptive approach and literature-based data collection techniques, the study finds that the curriculum is formulated through a combination of sharia and legal science-based courses. Integration is achieved through curriculum updates that serve as a competitive advantage for graduates. Future research may further examine the internal and external challenges faced in the process of integrating these bodies of knowledge.